Stress among nursing professionals at na HIV-Aids unit - Miquelim, Janice D.L.; Carvalho, Cleide B.O.; Gir, Elucir; Pelá, Nilza T.R. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: nursing is recognized as a stressful profession due to physical and mental overload, work load and the need to live with ill persons. Thesefacts become even worse in care for HIV/AIDS patients due to the high complexity of care, creating an intensive work environment as a result of the gra-vity of these patients’ condition. Objective:the aims of this investigation were to identify stress among nursing workers in care for HIV/AIDS patients andto verify the stress phase the affected professionals are in. This study was carried out at the HIV/AIDS unit of a University Hospital in the interior of SãoPaulo, Brazil, with hospitalization, day hospital and clinical care. Method:we studied 10 nurses and 37 nursing auxiliaries, using Lipp’s Stress SymptomInventory. Result:three (30%) nurses and 16 (48.5%) nursing auxiliaries displayed stress. With respect to work time, we observed that stress tends toappear earlier among nursing auxiliaries than among nurses. Among the 3 nurses, 2 (66.6%) were in the resistance phase, 1 (33.3%) in the near exhaustionphase and nobody in the exhaustion phase. 11 (68.7%) of the nursing auxiliaries were in the resistance phase, 4 (25%) in the near exhaustion phase and 1(6%) in the exhaustion phase. Conclusion:we conclude that stress in nursing professionals results in physical and psychological diseases, bringing them toa state of dissatisfaction, dismotivation and decreased productivity at work, besides other signals such as decreased “alertness and concentration”, whichare essential for carrying out their function.